Sistem Sertifikasi Halal dengen Sistem CEROL-SS23000 untuk Berbagai Kategori Produsen Pangan - Ha Phi Ro; Feri Kusnandar; Joko Hermanianto (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2017)
Consuming halal food is a mandatory for every muslim. For this reason, it is important for food producers to provide halal food. Demand of halal food increases significantly in line with the growth of muslim population and the awareness of muslim to consume halal food. Halal food production has become the concern of food producers in the last twenty years, including in Indonesia. The assurance of halal food production by food producers are applied through certification process. In Indonesia, the process of halal certification was conducted by the Indonesian Council of Ulama (MUI), namely the Institute for Foods, Drugs, and Cosmetics (LPPOM MUI). Indonesia has become the pioneer in the establishment of halal certification system. Currently LPPOM MUI has established Halal Certification Online Service System (CEROL-SS23000) in order to facilitate the halal certification process. This research studied the implementation of halal certification system for various food producer categories conducted by LPPOM MUI in applying the CEROL-SS23000 system. The primer data was obtained through survey to some categories of food producers to gain perception from food producers on the CEROL-SS23000 application. The survey showed that food producers satisfied with the CEROL-SS23000 system in facilitating the halal certification process.